Peanut Supply Chain Reinforcement Model - Dwi Ratna Hidayati (Universitas Prasetiya Mulya, 2019)
The study focused on reinforcement model establishment for peanut supply chain as one of potential exporting commodity due to the threat of global trade liberalization. As one of main peanut producer area, however, Bangkalan Regency has poor management along the chain with various problems internally and externally. The research involved primary data through both observation and in depth interview of several key informants at main producer area in Bangkalan Regency such as head of farmer groups, extension workers and local leaders. The strategic model analyzed by using SWOT analysis had resultedturn around strategy that emphasize consolidation and improvement of weaknesses while catching opportunities. Improvement of weaknesses strategies can be done by involving farmers into local base institution such as farmer group and cooperative group, providing farmers the literacy program, educating farmer on digital equipments for e-market preparation, and empowering micro scale business of peanut base material. Next, the opportunities considered to be taken are embracing middleman as partner, building peanut industry, distributing infrastructure improvement to remote agricultural area, providing information by having partnership with vendor such as XL and Telkomsel, and assisting farmer’s marketing institution in the operation.Keywords: supply chain, SWOT, reinforcement, empowering, communication(1) Department of Agribusiness, Trunojoyo University, Madura, Indonesia* Corresponding Author https://doi.org/10.21632/irjbs.12.1.55-68